(untitled) (Indian Journal of Chemistry (IJC), 2024)
The enhancement of intensity of the hypersensitive 5D0 → 7F2 transition in Eu3+ doped CaF2 nanoparticles (NPs) by exploitation of polarizability of the stabilizing ligands (ethylene glycol (EG), citrate (TSC) and EDTA) is reported. The correlation between the asymmetric ratio, R I(5D0→7F2)/I( 5D0→7F1) of the transition with the nature of the capping ligands is studied by determining Judd-Ofelt intensity parameter (Ω2), radiative transition probability (A) and average lifetime (τ). R is maximum for EDTA capped NPs followed by TSC and EG capped NPs. Bi-exponential fitting of the decay curves indicate the contribution of Eu3+ in the grain boundary to the R value is maximum for EDTA stabilized NPs. Cytotoxicity studies on epithelial human breast cancer cell (MDA 231) and RAW 264.7 cells suggested biocompatibility of 75% up to a maximum concentration 250 μg/mL. These characteristics show the potential of the synthesized nanoparticles in the fields of optical devices as well as bioimaging.